2016
DOI: 10.1111/jfpp.13145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poly(Lactic Acid)/Kenaf Composites Incorporated with Thymol on the Antimicrobial Activity of Processed Meat

Abstract: Bio‐based composites comprised of poly(lactic acid) (PLA), kenaf fibers and thymol were developed and their antimicrobial (AM) properties and stability under different storage conditions investigated. The composite films containing 20‐30% w/w thymol reduced E. coli in tryptone soy broth after two days at 37C and imparted a significant zone of inhibition in contact with E. coli inoculated plates. The composite films also reduced E. coli inoculated on the surface of processed sliced chicken samples after 30 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
(107 reference statements)
1
4
0
2
Order By: Relevance
“…The starch/CNF bionanocomposite film incorporated with 10 wt.% thymol exhibited the strongest antibacterial effect, as demonstrated by the largest clear zone of inhibition around the film (12.5 mm). These results were consistent with the findings of Tawakkal et al [ 16 ], who found that when the concentration of thymol was increased from 10% to 30% w/w in the PLA/kenaf films, the diameter of the inhibition zone increased from 7.5 mm to 20.6 mm at 20% w / w kenaf content. This was attributed to the volatile nature of thymol [ 22 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The starch/CNF bionanocomposite film incorporated with 10 wt.% thymol exhibited the strongest antibacterial effect, as demonstrated by the largest clear zone of inhibition around the film (12.5 mm). These results were consistent with the findings of Tawakkal et al [ 16 ], who found that when the concentration of thymol was increased from 10% to 30% w/w in the PLA/kenaf films, the diameter of the inhibition zone increased from 7.5 mm to 20.6 mm at 20% w / w kenaf content. This was attributed to the volatile nature of thymol [ 22 ].…”
Section: Resultssupporting
confidence: 93%
“…The bacterial count of the control group, on the other hand, increased with the storage time, and the meat was deteriorated by day 6. Furthermore, in a study conducted by Tawakkal et al [ 16 ], it was found that the population of E. coli decreased significantly upon the increase in thymol concentration from 10% to 30% w / w in PLA/kenaf films. For instance, by day 19 of reading, there were no colonies detected for the samples wrapped in the films containing 20% w / w kenaf and 30% w / w thymol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials were melted by preheating (150 °C for 3 min) without applying pressure and then pressed at the same temperature for 2 min with a force of 20 kN before quench cooling to 30 °C under pressure. Tawakkal et al [ 141 ] also studied the antimicrobial activity of PLA/kenaf/thymol against Escherichia coli bacteria and naturally occurring fungi. Films with higher thymol concentrations and higher kenaf loading exhibited excellent antibacterial properties against fungal growth due to the release of thymol into the headspace surrounding the samples; however, the shelf life after storage for 3 months at ambient temperature showed only a slight decrease in antimicrobial properties.…”
Section: Production Technologymentioning
confidence: 99%
“…Tawakkal uses PLA, kenaf fiber, and thymol as raw materials to prepare bio-based composite films; by adding 20% to 30% thymol, the film can maintain the number of E. coli in trypsinogen soybean soup at 37 °C for 2 days; the addition of natural fibres can reduce production costs and improve the mechanical properties of PLA; The addition of antibacterial agents such as essential oil extracts can further enhance packaging functions for better preservation of food. This research proposes a packaging system with enormous potential that uses bio-derived polymers (PLA) and natural fibres (kenaf) and essential oil extracts (thymol) as the basis for new materials that extend shelf life of meat products [24].…”
Section: Poly-lactic Acid (Pla)mentioning
confidence: 99%